Arctangent Summation

Geometry Level 4

n = 1 tan 1 ( 2 n n 4 + n 2 + 2 ) \large\displaystyle\sum_{n=1}^{\infty}\tan^{-1}\left(\dfrac{2n}{n^4+n^2+2}\right)

If the value of the summation above is in the form of a b π \dfrac ab\pi , where a a and b b are coprime positive integers, find a + b a+b .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Apr 16, 2016

Similar solution with Ikkyu San 's, different presentation.

S = lim m n = 1 m tan 1 ( 2 n n 4 + n 2 + 2 ) = lim m n = 1 m tan 1 ( ( n 2 + n + 1 ) ( n 2 n + 1 ) 1 + ( n 2 + n + 1 ) ( n 2 n + 1 ) ) = lim m n = 1 m ( tan 1 ( n 2 + n + 1 ) tan 1 ( n 2 n + 1 ) ) = lim m ( n = 1 m tan 1 ( n 2 + n + 1 ) n = 1 m tan 1 ( n 2 n + 1 ) ) = lim m ( n = 1 m tan 1 ( n 2 + n + 1 ) n = 0 m 1 tan 1 [ ( n + 1 ) 2 ( n + 1 ) + 1 ] ) = lim m ( n = 1 m tan 1 ( n 2 + n + 1 ) n = 0 m 1 tan 1 ( n 2 + n + 1 ) ) = lim m ( tan 1 ( m 2 + m + 1 ) tan 1 ( 0 2 + 0 + 1 ) ) = tan 1 ( ) tan 1 ( 1 ) = π 2 π 4 = π 4 \begin{aligned} S & = \lim_{m \to \infty} \sum_{n=1}^m \tan^{-1} \left(\frac{2n}{n^4+n^2+2} \right) \\ & = \lim_{m \to \infty} \sum_{n=1}^m \tan^{-1} \left(\frac{\color{#3D99F6}{(n^2+n+1)} - \color{#D61F06}{(n^2-n+1)}}{1+\color{#3D99F6}{(n^2+n+1)} \color{#D61F06}{(n^2-n+1)}} \right) \\ & = \lim_{m \to \infty} \sum_{n=1}^m \left(\tan^{-1} \color{#3D99F6}{(n^2+n+1)} - \tan^{-1} \color{#D61F06}{(n^2-n+1)} \right) \\ & = \lim_{m \to \infty} \left( \sum_{n=1}^m \tan^{-1} (n^2+n+1) - \sum_{n=1}^m \tan^{-1} (n^2-n+1) \right) \\ & = \lim_{m \to \infty} \left( \sum_{n=1}^m \tan^{-1} (n^2+n+1) - \sum_\color{#D61F06}{n=0}^\color{#D61F06}{m-1} \tan^{-1} [(\color{#D61F06}{n}+1)^2-(\color{#D61F06}{n}+1)+1] \right) \\ & = \lim_{m \to \infty} \left( \sum_{n=1}^m \tan^{-1} (n^2+n+1) - \sum_{n=0}^{m-1} \tan^{-1} (n^2+n+1) \right) \\ & = \lim_{m \to \infty} \left(\tan^{-1} (m^2+m+1) - \tan^{-1} (0^2+0+1) \right) \\ & = \tan^{-1} (\infty) - \tan^{-1} (1) = \frac{\pi}{2} - \frac{\pi}{4} = \frac{\pi}{4} \end{aligned}

a + b = 1 + 4 = 5 \Rightarrow a + b = 1 + 4 = \boxed{5}

Ikkyu San
Apr 15, 2016

n = 1 tan 1 ( 2 n n 4 + n 2 + 2 ) = n = 1 tan 1 ( ( n 2 + n + 1 ) ( n 2 n + 1 ) 1 + ( n 2 + n + 1 ) ( n 2 n + 1 ) ) = lim m n = 1 m [ tan 1 ( n 2 + n + 1 ) tan 1 ( n 2 n + 1 ) ] = lim m [ tan 1 ( 3 ) tan 1 ( 1 ) + tan 1 ( 7 ) tan 1 ( 3 ) + tan 1 ( 13 ) tan 1 ( 7 ) + + tan 1 ( m 2 + m + 1 ) tan 1 ( m 2 m + 1 ) ] = lim m [ tan 1 ( m 2 + m + 1 ) tan 1 ( 1 ) ] = π 2 π 4 = π 4 \begin{aligned}\displaystyle\sum_{n=1}^{\infty}\tan^{-1}\left(\dfrac{2n}{n^4+n^2+2}\right)=&\displaystyle\sum_{n=1}^{\infty}\tan^{-1}\left(\dfrac{(n^2+n+1)-(n^2-n+1)}{1+(n^2+n+1)(n^2-n+1)}\right)\\=&\displaystyle\lim_{m\to\infty}\sum_{n=1}^m\left[\tan^{-1}(n^2+n+1)-\tan^{-1}(n^2-n+1)\right]\\=&\displaystyle\lim_{m\to\infty}\bigg[\tan^{-1}(3)-\tan^{-1}(1)+\tan^{-1}(7)-\tan^{-1}(3)+\tan^{-1}(13)-\tan^{-1}(7)+\cdots+\\&\tan^{-1}(m^2+m+1)-\tan^{-1}(m^2-m+1)\bigg]\\=&\displaystyle\lim_{m\to\infty}\bigg[\tan^{-1}(m^2+m+1)-\tan^{-1}(1)\bigg]\\=&\dfrac{\pi}2-\dfrac{\pi}4=\dfrac{\pi}4\end{aligned}

Thus, a + b = 1 + 4 = 5 a+b=1+4=\boxed5


Notes:

tan 1 ( x ) tan 1 ( y ) = tan 1 ( x y 1 + x y ) \tan^{-1}(x)-\tan^{-1}(y)=\tan^{-1}\left(\dfrac{x-y}{1+xy}\right)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...